Crystallization behavior of polypropylene/graphene nanoplatelets composites. Issue 3 (26th October 2018) - Beuguel, Quentin; Boyer, Séverine A. E.; Settipani, Daniel; Monge, Gabriel; Haudin, Jean‐Marc; Vergnes, Bruno; Peuvrel‐Disdier, Edith
Abstract : Interest in graphite fillers has grown since the separation of graphene from graphite by micromechanical cleavage. The object of the article is to understand the influence of graphene nanoplatelets (GNPs) with different sizes on the crystallization behavior of a polyolefin matrix such as polypropylene (PP), after elaboration by melt mixing and compression molding. Composites with volume fractions of graphene nanoplatelets ranging from 0.3 to 2 vol% were prepared. The particle dispersion states in the composites were characterized at different scales using Scanning and Transmission Electron Microscopies (SEM and TEM). Polypropylene crystallization and orientation were investigated using optical microscopy, Differential Scanning Calorimetry (DSC) and X‐ray diffraction. This article discusses the strong acceleration of crystallization kinetics because of the presence of GNPs. The micrometric flake‐shaped GNPs act as nucleating agent and induce an epitaxial growth of alpha ( α ) crystalline phase of PP. The nucleating effect is related to the surface of the particles available for heterogeneous nucleation. Radial spherulitic growths are observed from the smallest micrometric particles. The coarsest GNPs, easily oriented by flow, favor PP transcrystallinity, in such a way that (010) plane of PP is parallel to (001) plane of graphene nanoplatelets. Abstract : The effect of microscale aggregated graphenes (GNPs) on polypropylene crystallization is shown. The microscale particles clearly affect the nucleation step. The nucleation efficiency is linked to the surface developed by the microscale GNP particles. The smaller the size of the GNP particles is, the larger the number of nuclei and the smaller the spherulite. The flow orientates microscale anisotropic particles (flakes) which results in transcrystallinity, (010) plane of PP parallel to (001) plane of GNPs.